Huxley’s Ape and Essence and human manipulation - Babaee, Ruzbeh; Wan Yahya, Wan Roselezam (SciPress, 2014)
In Ape and Essence (1948), Aldous Huxley indicates that people and their lives are highly controlled and regulated by disciplinary systems. Not only are people‟s minds controlled by the disciplines, but also physical bodies are disciplined into submission and literally taken away from their rightful owners. In fact, in Belial society of Ape and Essence, people are considered as the property of the State. Thus, their goals and ambitions revolve around satisfying the States needs. This present study shows the impacts of disciplinary systems- as a consequence of nuclear bomb- on humanity, and investigates the ways through which human beings are manipulated in Ape and Essence.